Modern Confucian Mou Zongsan’s Negation of “Cognitive Awareness” - İlknur Sertdemir (Şarkiyat Mecmuası)
The early twentieth century in mainland China exemplifies the modernization process in many areas, including language, literature, traditional thought, education, and even the political system. Among these reformist movements, it is important to note that this movement of thought was established under the name of New Confucianism, which dates back to the ancient ages, was based on Confucius (479–551 BC), and was widely adopted by the human nature view of Mencius (372–289 BC). Unlike Confucius’ normative moral sentiment, this new movement is more akin to Mencius’ innatist theory. Xiong Shili (1885–1968), who established the foundations of New Confucianism, emphasized the conceptof “self,” which can be found in Mencius’ doctrine and may correspond to the heart–mind correlation. Mou Zongsan (1909–1995), one of the movement’s later representatives, is regarded as the most effective intellectual of the time for his remarkable comments on heart–mind correlation and self-cultivation. Mou philosophy includes some hypothetical arguments that explain the cognitive and affective processes in completely different stages, contrary to Mencius’s view of integration; coordinate those stages with the two-tiered nature of the self; and equate existential essence with the essence of human nature. In this study, the how of the sense of self will be examined in relation to the Mou philosophy’s ontocosmological approach, and the details of the thesis that negates cognitive awareness in internalizing knowledge and virtue, which are assumed to be innate, will be analyzed.